2017
DOI: 10.1177/0163278716686809
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions and Malpractices Toward Antibiotic Use in Childhood Upper Respiratory Tract Infections Among a Cohort of Lebanese Parents

Abstract: Antimicrobial resistance is an emerging global health threat. Misuse and abuse of antibiotics are of particular concern in the pediatric population. Since management of childhood illnesses depends considerably on parents' perceptions, the objectives of this study were to report parents' perspectives and assess their practices toward antibiotics used for upper respiratory tract infections (URTIs) in children. Using a cross-sectional design, anonymous structured questionnaires were completed by 1,037 parents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 28 publications
0
31
0
1
Order By: Relevance
“…No study to date has evaluated the impact of leftover antibiotics on resistance. Other patient factors are related to the inadequate duration of therapy, inappropriate indication for use, non-adherence to the antibiotic regimens, and lack of awareness about antibiotic uses [ 29 ]. In the hospital sector, it is found that, in addition to the prescriber factors listed above, drivers of resistance may be due to poor applicability of antibiotic stewardship programs, poor infection control and prevention practices and the selection pressure due to the misuse and abuse of disinfectants and decontaminants [ 30 ].…”
Section: Antimicrobial Resistance In Lmicsmentioning
confidence: 99%
“…No study to date has evaluated the impact of leftover antibiotics on resistance. Other patient factors are related to the inadequate duration of therapy, inappropriate indication for use, non-adherence to the antibiotic regimens, and lack of awareness about antibiotic uses [ 29 ]. In the hospital sector, it is found that, in addition to the prescriber factors listed above, drivers of resistance may be due to poor applicability of antibiotic stewardship programs, poor infection control and prevention practices and the selection pressure due to the misuse and abuse of disinfectants and decontaminants [ 30 ].…”
Section: Antimicrobial Resistance In Lmicsmentioning
confidence: 99%
“…Chamoun et al have reported in 2016, based on a study about the prevalence of antibiotic resistance in 76, 278 isolated bacterial strains obtained from 16 Lebanese hospitals (between the years 2013 and 2016), that antimicrobial resistance is becoming a major problem in Lebanon [14]. In 2017, a study conducted by El Khoury and collaborators, concluded that the low educational and socioeconomic levels of parents as factors significantly associated with poor knowledge and misuse regarding antibiotics [15]. Cheaito and colleagues, in 2014, conducted a survey among buyers of antibiotics in pharmacies.…”
Section: Introductionmentioning
confidence: 99%
“…Respondents to this study reported that they would prescribe antibiotics to 30% of affected patients compared to 40% in the study by Liu, et al [12]. These misconceptions and the subsequent practice of providing antibiotics may be important factors behind the increase in antibiotic resistance [7,25]. In particular, healthcare professionals should be reminded that routinely administering antibiotics is not recommended for all febrile respiratory conditions.…”
Section: Discussionmentioning
confidence: 99%